2018
DOI: 10.1107/s2059798318001754
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the type III pullulan hydrolase fromThermococcus kodakarensis

Abstract: Pullulan-hydrolysing enzymes, more commonly known as debranching enzymes for starch and other polysaccharides, are of great interest and have been widely used in the starch-saccharification industry. Type III pullulan hydrolase from Thermococcus kodakarensis (TK-PUL) possesses both pullulanase and α-amylase activities. Until now, only two enzymes in this class, which are capable of hydrolysing both α-1,4- and α-1,6-glycosidic bonds in pullulan to produce a mixture of maltose, panose and maltotriose, have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…Salt bridges in enzyme may contribute to its stability at high temperature (Vieille and Zeikus, 2001;Kundu and Roy, 2010). Recently, Guo et al (2018) summarized factors may contribute to the thermostability for pullulan-hydrolyzing enzymes. They found that there are more salt bridges in thermophilic pullulan-hydrolyzing enzymes than mesophilic ones, suggesting the importance of salt bridge for the enzyme pullulan-hydrolyzing thermostability.…”
Section: Salt Bridge Interaction Analysismentioning
confidence: 99%
“…Salt bridges in enzyme may contribute to its stability at high temperature (Vieille and Zeikus, 2001;Kundu and Roy, 2010). Recently, Guo et al (2018) summarized factors may contribute to the thermostability for pullulan-hydrolyzing enzymes. They found that there are more salt bridges in thermophilic pullulan-hydrolyzing enzymes than mesophilic ones, suggesting the importance of salt bridge for the enzyme pullulan-hydrolyzing thermostability.…”
Section: Salt Bridge Interaction Analysismentioning
confidence: 99%
“…TIM-barrel) type catalytic domain; (iii) their primary structures contain the four highly conserved sequence regions; and (iv) their catalytic triad is constituted by the three acidic residues (two aspartic acids and one glutamic acid). Biochemical characterization and three-dimensional structure analysis of TK-PUL revealed that it possessed all the features of the family GH13 [3,8].…”
Section: Tk-pul and Sequence-based Classificationmentioning
confidence: 99%
“…Because of this novel domain, monomers of archaeal enzymes remain successful to adopt a unique active-site configuration for cyclodextrinase activity [24,25]. Tertiary structure of TK-PUL [8] was found similar with the structures of other archaeal members of the subfamily GH13_20, which are maltogenic amylase from Staphylothermus marinus [24] and α-amylase/cyclomaltodextrinase from Pyrococcus furiosus [25]. TK-PUL lacks significant homology with these enzyme at the N-terminal region and probably due to this reason TK-PUL, in spite of high cyclodextrinase activity [3], is not a member of either CBM34 or CBM48 (http://www.cazy.org/).…”
Section: Tk-pul and Sequence-based Classificationmentioning
confidence: 99%
See 2 more Smart Citations